Arabidopsis PCaP2 Plays an Important Role in Chilling Tolerance and ABA Response by Activating CBF- and SnRK2-Mediated Transcriptional Regulatory Network - Wang, Xianling; Wang, Lu; Wang, Yu; Liu, Huan; Hu, Dan; Zhang, Ning; Zhang, Shaobin; Cao, Huiying; Cao, Qijiang; Zhang, Zhihong; Tang, Shuang; Song, Dandan; et al. (Frontiers in Plant Science, 2018)
Chilling stress affects plant growth and productivity. However, the multi-underlying mechanisms of chilling tolerance are not well understood. Arabidopsis PCaP2 is involved in regulating the dynamic of microtubules and F-actin and Ca2+-binding ability. Here, the results showed that the PCaP2 expression was highly induced in roots, cotyledons, true leaves, lateral roots and flowers under cold stress. Compared with the wild type, PCaP2-overexpressing plants displayed the enhanced tolerance, whereas its RNAi and mutant were more sensitive in seed germination, seedling and reproductive growth under chilling stress in Arabidopsis. In addition, PCaP2 was also a positive regulator of ABA signaling pathway by analyzing the expression of PCaP2 and the phenotypes of PCaP2-overexpressing, mutant and RNAi plants under ABA treatment. Interestingly, disruption of PCaP2 inhibited the expression of CBF1, -3 and CBF-target COR genes, while increased the CBF2 expression in response to cold or ABA. Moreover, we found that SnRK2s were involved in cold stress and PCaP2 mutants down-regulated the transcription level of SnRK2.2, -2.3 and SnRK2-mediated downstream genes including ABF2, RD29A, KIN1, KIN2, but up-regulated SnRK2.6, ABF1, -3, -4 in ABA and cold treatments. It is well-accepted that PCaP2 as a Ca2+-binding protein triggers the gene expression to enhance plant chilling tolerance. Our further studies showed that microtubule destabilizing activity of PCaP2, but not F-actin-severing function, may be involved in chilling stress. Taken together, our results highlight that PCaP2 plays an important role in chilling tolerance and ABA response by triggering the CBF- and SnRK2-meditated transcriptional regulatory pathways, providing novel evidences of underlying mechanisms of multi-pathways in chilling stress.